The relationship between the technology acceptance model and preference for ebooks at a large research university. Issue 3 (7th May 2019) - Smith, Susan Lynn; Rodriguez, Allyson; Miller, Erin DeWitt; Xu, Lu
Abstract : Purpose: This study aims to uncover factors related to students' preference for ebooks with hopes that understanding what drives these preferences will help librarians to figure out how to increase students' use of ebooks. Design/methodology/approach: Based on the unified theory of acceptance and use of technology, researchers developed a model of ebook preference and a survey including constructs related to perceived usefulness and perceived ease of use. Respondents were undergraduate students from a core political science course at a large research university in the USA. Findings: Ebook performance expectancy and ebook self-efficacy have indirect effects on ebook preference by way of ebook attitude. Ebook attitude and social influence both have direct effects. Research limitations/implications: One of the limitation include respondents being of a similar age and having a similar experience of technology and ebooks. Prior use of ebooks may partially explain the results. Practical implications: Librarians should help students develop ebook self-efficacy. Vendors should consider how interfaces may impact ebook self-efficacy. Ebook attitude may be positively influenced by tapping students' desire to utilize technology. Originality/value: This research adds to the understanding about ebook preference while expanding research in libraries by applying a theory and model from another research discipline.